Gest??o de projetos em institui????es de ensino superior: caso pr??-administra????o - Costa, Giovane da (2012)
As a result of social changes, the HEIs (Higher Education Institutions) have been forced to evolve. The future of the institution depends on how well it adapts to changes in society. In this time of great changes, such as globalization, high competitiveness and growing quest for knowledge, HEIs (higher education institutions) need to be managed efficiently and effectively. Currently the reshaping of academic governance and management is aimed to improve performance and meet the expectations of all stakeholders, internal and external. It is in this context that the traditional forms of academic management are seen as outdated and ineffective, being gradually replaced by practices based on criteria of economic rationality. One of the management practices of the corporate model that has been imported into the academic model is the Project Management. It is in this context that this study seeks to identify how the IES conduct their projects through a case study of one of the projects Pr??-Administra????o CAPES (Coordination of Improvement of Higher Education Personnel) led by the University Nine July. Furthermore, based on the best practices of Project Management will identify possible improvements in the development of this academic project. The study is characterized by empirical research, exploratory and unique case. This research also aims to investigate the perception of social subjects involved in the research environment, on Project Management in Higher Education Institutions in this way is characterized by qualitative research, which according Godoy (1995) studies of this type involve obtaining data descriptive about places, people, organizations and forms of interaction that occur alert by direct contact with the researcher studied the situation. Data collection took place thru research and analysis bilbiogr??fica decumental, plus an interview and observations. The main results of the research show that the project was divided into subprojects and cores, where the coordinators of these subprojects had full autonomy in the conduct. Furthermore, the project is part of a complex institution and adhocratica where relations of monitoring and control are not very clear, so it is recommended that in projects of this nature are made available resources and attention to the monitoring and control activities.